rag1999
rag1999
02-05-2018
Mathematics
contestada
h^-2g for h=3 and g=27
Respuesta :
Аноним
Аноним
02-05-2018
Plug h = 3 and g = 27 into the expression:
[tex]h^{-2}g= \dfrac{g}{h^2} = \dfrac{27}{3^2} = \dfrac{27}{9} = 3[/tex]
Answer Link
VER TODAS LAS RESPUESTAS ( 52+ )
Otras preguntas
Please help me out????
reduced ratio of 2:10:14
Which description best suits the format of As-if exercises? A. Actors will develop a gesture symbolic of the psycho-physical aspect of the character. B. Acto
Write 40% as a fraction in simplest form.
please HELP!!! this is my final grade pleaseidentify the fallacy in the following example:"Candidate X doesn't have children, so she doesn't understand family v
What is the 8th term of the geometric sequence with this explicit formula? an= 7• (-2) (n - 1)
Formal Standard English and Standard English are the same thing. True False
what is the counter-argument of an persuasive essay?
Simplify the radical
Two more than the quotient of a number 9 is 8